2017
DOI: 10.3917/mana.204.0322
|View full text |Cite
|
Sign up to set email alerts
|

Next steps in organizing alternatives to capitalism: toward a relational research agenda

Abstract: In the last ten years, the latest acute economic crisis of global capitalism has put in check most of the institutional pillars of the post-Keynesian consensus: globalization, free trade, free movement of capital and labor, and so on. Status quo response to the crisis was the enforcement of austerity economic models, cutting public budgets and curbing public services. Those economic models remain the dominant ways of thinking in the post-2008 crisis (Davis, 2009). Austerity was not only prescribed to the indeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 52 publications
1
17
0
2
Order By: Relevance
“…Despite the different nature of their theoretical approaches and empirical cases, all three articles included here touch upon the relation between the organizations they study and the wider economic, social and institutional context in which they are embedded. Barin-Cruz et al (2017) correctly point to the importance of examining this relation more closely. Delineating a research agenda on alternative economies in organization studies, they identify four key stakeholders that deserve our attention: governments, civil society, investors and universities.…”
Section: Three Papers Further Expanding the Post-capitalist Archivementioning
confidence: 97%
See 1 more Smart Citation
“…Despite the different nature of their theoretical approaches and empirical cases, all three articles included here touch upon the relation between the organizations they study and the wider economic, social and institutional context in which they are embedded. Barin-Cruz et al (2017) correctly point to the importance of examining this relation more closely. Delineating a research agenda on alternative economies in organization studies, they identify four key stakeholders that deserve our attention: governments, civil society, investors and universities.…”
Section: Three Papers Further Expanding the Post-capitalist Archivementioning
confidence: 97%
“…Especially this last ecosystem is of particular importance, as alternative organizations’ relations to existing institutional actors – e.g. the university (Esper et al, 2017), investors (Meyer and Hudon, 2017), the state, and civil society (Barin-Cruz et al, 2017), but also social movements, trade unions and political parties (De Coster and Zanoni, 2018; Husted and Plesner, 2017) – are key not only for their existence but also for their ability to challenge the capitalist economy (Miller, 2015). As critics have observed, the political antagonism of alternative economy organizations should not be assumed, but rather needs to be constructed (Böhm, 2014; Dean, 2015a, 2015b).…”
Section: Three Papers Further Expanding the Post-capitalist Archivementioning
confidence: 99%
“…There are at least three ways to conceptualize the notion of alternative organizational forms (Elinger et al, 2011). The first group of studies which we have identified points at differences in understanding of the types of alternative organizational forms and their businesses as well (Cruz et al, 2017, Jasińska-Biliczak et al, 2017. In this…”
Section: Literature Reviewmentioning
confidence: 99%
“…The limitations of critical diversity research have become particularly apparent in the wake of the economic crisis of 2008. While the crisis triggered a surge in research on the role of organizations in sustaining and exacerbating societal inequality (Amis, Mair, & Munir, 2020; Bapuji, Ertug, & Shaw, 2020; Dunne, Grady, & Weir, 2018) and postcapitalist, alternative organizing for social justice (Barin‐Cruz, Aquino Alves, & Delbridge, 2017; Zanoni, Contu, Healy, & Mir, 2017), it did not substantially affect critical diversity research. We still miss a conceptual vocabulary for setting up an emancipatory social justice agenda amidst and beyond capitalism (Holck, 2018a, 2018b; Janssens & Zanoni, forthcoming).…”
Section: The Rise Of Diversity and The Demise Of Classmentioning
confidence: 99%